International diversification versus domestic diversification: Mean-variance portfolio optimization and stochastic dominance approaches - Fathi Abid; Pui Lam Leung; Mourad Mroua; Wing Keung Wong (Journal of Risk and Financial Management, 2014)
This paper applies the mean-variance portfolio optimization (PO) approach and the stochastic dominance (SD) test to examine preferences for international diversification versus domestic diversification from American investors' viewpoints. Our PO results imply that the domestic diversification strategy dominates the international diversification strategy at a lower risk level and the reverse is true at a higher risk level. Our SD analysis shows that there is no arbitrage opportunity between international and domestic stock markets; domestically diversified portfolios with smaller risk dominate internationally diversified portfolios with larger risk and vice versa; and at the same risk level, there is no difference between the domestically and internationally diversified portfolios. Nonetheless, we cannot find any domestically diversified portfolios that stochastically dominate all internationally diversified portfolios, but we find some internationally diversified portfolios with small risk that dominate all the domestically diversified portfolios.
Keywords: C14; G11; G12; G14; G15; 330; international diversification; domestic diversification; mean-variance portfolio optimization; stochastic dominance